400 EFFECTS OF HEALTH INSURANCE ON AFRICAN AMERICAN PATIENTS WITH CHRONIC KIDNEY DISEASE. (1st January 2005) - Gowdy, O.; Flessner, M.
Abstract : Health care disparities have a direct impact on the health of patients. We hypothesize that health insurance has a significant effect on African American patients with chronic kidney disease (CKD). To test the hypothesis, the following data from 393 patients with MDRD-estimated glomerular filtration rate (GFR, mL/min/1.73 m2) of > 7 but < 75 were examined with ANOVA with insurance (INS) as the independent factor: age, systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP), serum creatinine (SCr), MDRD-GFR, and compliance with appointments and medications. 297 patients had insurance (200-Medicaid, age 56 ± 1; 32-Medicare, age 66 ± 2; 65-private, age 51 ± 2), while 96 (24%, age 47 ± 1) had no insurance (p < .0001, age vs INS). While there was no significant correlation of SCr with INS, there was a significant correlation of MDRD-GFR with INS (p < .002) with the highest functional level (44 ± 2) with privately insured and the lowest (35 ± 1) in the medicaid group. There were no significant differences in blood pressure versus INS. The uninsured had the highest rate of missed appointments/year (2.24 ± 0.24) and poorest medication noncompliance (21.8 ± 0.4%) when compared to each other group or to all insured (1.75 ± 0.21 missed visits, p = .05; 12.5 ± 3.4% medication noncompliance, p < .003). The GFR was negatively associated with the number of missed appointments (p < .001). In conclusion, insurance status in African American CKD patients does correlate with GFR but not with blood pressure. The lack of insurance is present in younger patients and directly impacts compliance with medical visits and therapy. Lack of compliance is strongly correlated with a lower GFR.